Mechanization and Postharvest Management to Support Sustainable and Low Carbon Rice Production - Nguyen Van Hung; Nguyen Thanh Nghi; Nguyen Van Hieu; Tran Thi Cam Nhung; Balingbing, Carlito; Sandro, Joseph; Gummert, Martin; Kumar, Virender (2023)
Rice production in Asia and Africa has faced labor shortages and climate change issues such as unanticipated droughts and floods, causing unstable yields and a high risk of crop losses. In addition, low farming efficiency, high carbon footprint, and high postharvest losses are the major constraints in rice production. Low farming efficiency (high energy and labor cost and agronomic input use) is mainly caused by poor land consolidation, lack of precision land leveling, crop establishment, and crop care. These inefficient practices and poor water and rice straw management cause a high carbon footprint. Furthermore, poor harvest and postharvest management also cause high postharvest losses (more than 10%) and significantly contribute to rice carbon footprint. This document introduces several mechanization and postharvest solutions to address the said challenges and problems, which have been developed by IRRI and country partners.